GAMBARAN SYMPATHETIC SKIN RESPONSE PADA STROKE ISKEMIK - Melke J Tumboimbela*, Bob Santoso Wibowo**, Freddy Sitorus**, Joedo Prihartono*** (Neurona Majalah Kedokteran Neuro Sains, 2009)
BACKGROUND AUTONOMIC DISTURBANCE IS ONE OF THE COMMON CLINICAL FEATURE IN STROKE BUT THERE WAS A SMALL ATTENTION ATTENTION HAS BEEN GIVEN AS TO VARIOUS FEATURES OF SYMPATHETIC DYSFUNCTION SUCH AS SUDOMOTOR DYSREGULATION IN CEREBROVASCULAR DISEASES ALTHOUGH THE EXACT PATHOGENESIS OF THESE DISORDERS IS UNCERTAIN IT HAS BEEN SUGGESTED THAT SOME OF THESE SYMPTOMS HAVE COMMONLY BEEN ASSOCIATED WITH INCREASED ACTIVITY OF THE SYMPATHETIC NERVOUS SYSTEM SYMPATHETIC SKIN RESPONSE SSR IS ONE OF ELECTROPHYSIOLOGY METHODS TO EVALUATE SYMPATHETIC FUNCTION